A Review on Research Trend on Sigatoka Diseases from 1965 -2018: Bibliometric Approach - et. al., Erere Avwerosuo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sigatoka is major disease in banana and plantain production globally. The objective of this study is to analyze the trend at which sigatoka diseases is going, based on that, several components were retrieved from Scopus database during the period of 1961 – 2018. Specific keywords that contained “sigatoka” and “mycosphaerella “were formulated to retrieve relevant documents from the Scopus database. A total of 256 documents were analyzed. This component included most prolific authors, country productivity in sigatoka disease, keyword, document types and source type and citations from publications were also analyzed. Leading institutions also determined based on their volume of publications in black sigatoka disease. Brazil had the highest number of publication with 54 and 320 citations, followed by United State with 39 publications, 669 citations. Nigeria is the only Africa country among the Top 10 countries in black sigatoka disease research during the period of this study. The most productive author is Ortíz, Rodomiro with 12 publications (328 citations). Consequently, CIRAD Centre de Recherche de Montpellier is the most productive affiliation/ institution with a number of 21 documents published. 2009 and 2016 are the most productive year in this subject domain since 1961. Acta Horticulturae is the leading source outlet used by black sigatoka disease researcher with 21 documents published and 79 citations. A total of 252 authors contributed to sigatoka disease 1961. This study reveals research gaps in black sigatoka disease. Also, provide platform for standard research work. Sigatoka is major disease in banana and plantain production globally.